2015
DOI: 10.1063/1.4926925
|View full text |Cite
|
Sign up to set email alerts
|

Photo-assisted intersystem crossing: The predominant triplet formation mechanism in some isolated polycyclic aromatic molecules excited with pulsed lasers

Abstract: Naphthalene, anthracene, and phenanthrene are shown to have very long-lived triplet lifetimes when the isolated molecules are excited with nanosecond pulsed lasers resonant with the lowest singlet state. For naphthalene, triplet state populations are created only during the laser pulse, excluding the possibility of normal intersystem crossing at the one photon level, and all molecules have triplet lifetimes greater than hundreds of microseconds, similar to the behavior previously reported for phenylacetylene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…This process requires less energy than that S 0 → S 1 transition via photon excitation (e.g., ca. 2.97 eV for anthracene) 65 . After intersystem crossing, one of the anthracene-based blades may undergo a non-radiative transition to the triplet excited state ( T 1 ) and change its spin multiplicity.…”
Section: Resultsmentioning
confidence: 99%
“…This process requires less energy than that S 0 → S 1 transition via photon excitation (e.g., ca. 2.97 eV for anthracene) 65 . After intersystem crossing, one of the anthracene-based blades may undergo a non-radiative transition to the triplet excited state ( T 1 ) and change its spin multiplicity.…”
Section: Resultsmentioning
confidence: 99%
“…In [34] it is indicated that autoionization of anthracene and naphthalene with 1-2 eV of vibrational energy only takes place for energies up to 0.1 eV below the ionization threshold. Furthermore, the character of the state which dominates the absorption at 7.94 eV is that of a valence state (8 1 A(V 3 )).…”
Section: Discussionmentioning
confidence: 99%